Adenine-induced animal model of chronic kidney disease: current applications and future perspectives - Yang, Qiao; Su, Songya; Luo, Nan; Cao, Gang (Renal failure, 2024)
Chronic kidney disease (CKD) with high morbidity and mortality all over the world is characterized by decreased kidney function, a condition which can result from numerous risk factors, including diabetes, hypertension and obesity. Despite significant advances in our understanding of the pathogenesis of CKD, there are still no treatments that can effectively combat CKD, which underscores the urgent need for further study into the pathological mechanisms underlying this condition. In this regard, animal models of CKD are indispensable. This article reviews a widely used animal model of CKD, which is induced by adenine. While a physiologic dose of adenine is beneficial in terms of biological activity, a high dose of adenine is known to induce renal disease in the organism. Following a brief description of the procedure for disease induction by adenine, major mechanisms of adenine-induced CKD are then reviewed, including inflammation, oxidative stress, programmed cell death, metabolic disorders, and fibrillation. Finally, the application and future perspective of this adenine-induced CKD model as a platform for testing the efficacy of a variety of therapeutic approaches is also discussed. Given the simplicity and reproducibility of this animal model, it remains a valuable tool for studying the pathological mechanisms of CKD and identifying therapeutic targets to fight CKD.